Sexual dimorphism in digit lengths in South American lizards: relationships with environment and embryonic development - Cipriano, Ana Paula (2023)
The sexual dimorphism in digit ratio was extensively investigated in humans. Traditionally, the second digit (index finger) and the fourth digit (ring finger) lengths are calculated in a ratio (2D:4D), in which men have higher DIV than women. The dimorphism in digit lengths is associated with the levels of steroid hormones during the embryonic development and likely does not change during adulthood, being established prenatally. Although the relationship between digit ratio and hormonal dynamics is considered consistent, the association with parameters that might affect the steroid levels, such as climatic and reproductive ones, is still unexplored. Several studies with Tetrapoda show that the dimorphism in digit lengths is different amidst species. It is possible that all digits may have the sensitivity to steroid hormones and the dimorphism may vary even between manus and pes in the same species. Our study compiled morphological, climatic, and reproductive databases to explore the sexual dimorphism in digit lengths in South American lizards of the genera Liolaemus and Tropidurus. Results indicate that the dimorphism is not conserved and all digits can be dimorphic when comparing different lizards species and populations. Furthermore, the reproductive mode can be playing a role in the dimorphism due to the distinct developmental conditions, and viviparous lizards can have different digits patterns when compared to oviparous ones. Our study also analyzed the effects of different thermal regimes during embryonic development. The neonates investigated are monomorphic for all the phenotypic traits studied, regardless of incubation temperature. On the other hand, the androgen receptors in Digit IV are already different between male and female since hatch, indicating the role of hormonal interactions in shaping the morphology along ontogeny. In this context, this study provided a different perspective to investigate the role of climate parameters, developmental dynamics, and how the dimorphism in digit lengths is established in different levels of biological organization. As our main contributions, we explored for the first time the role of environmental and reproductive parameters in the sexual dimorphism in digit lengths and indicated the probable effects of steroid receptors in phenotypic traits establishment in lizards.